Role of Global Food Security in the Common Agrarian Policy of the European Union - I. N. Shcherbak (Vestnik MGIMO-Universiteta)
The author devoted his research to the role of the global food security in the priorities of the Common Agricultural Policy of the European Union (CAP). The research sheds light on the parameters of the Common Agricultural Policy and the basic steps on the path of its reform. The research demonstrates that the priorities of the EC are mainly concentrated on achieving food security for the member-states of the EC, its population and the interests of the agricultural sector. The modern challenges to the Global Food Security (global food crises of 2007-2009, acute food shortages and hunger in crises regions of Africa and chronic malnutrition) are placed high on the agenda of the CAP. In this situation, the EU is trying in the interests of stabilization of the world agricultural market to solve simultaneously the tasks of providing assistance for development and mitigation of the threats to the Global Food security. The deepening rift between the strategy of the CAP oriented towards promotion of agricultural export and real contribution of the EC to the Global Food Security and assistance for development is becoming more and more the most «vulnerable» place of the CAP.